2022
DOI: 10.1073/pnas.2207009119
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin structure undergoes global and local reorganization during murine dendritic cell development and activation

Abstract: Classical dendritic cells (cDCs) are essential for immune responses and differentiate from hematopoietic stem cells via intermediate progenitors, such as monocyte−DC progenitors (MDPs) and common DC progenitors (CDPs). Upon infection, cDCs are activated and rapidly express host defense-related genes, such as those encoding cytokines and chemokines. Chromatin structures, including nuclear compartments and topologically associating domains (TADs), have been implicated in gene regulation. However, the extent and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 69 publications
(87 reference statements)
0
9
0
Order By: Relevance
“…In this study PU.1 was found to regulate chromatin remodeling between the –50 kb enhancer and the Irf8 promoter in myeloid differentiation. In a recent study Kurotaki et al, 2022 determined the higher-order chromatin structure in DC progenitors, cDC1 and cDC2 on a genome-wide scale by Hi-C. In this study, reorganization of chromatin conformation at DC-specific gene loci was observed during cDC differentiation, and IRF8 was found to promote chromatin activation in DC progenitors leading to cDC lineage-specific gene expression.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…In this study PU.1 was found to regulate chromatin remodeling between the –50 kb enhancer and the Irf8 promoter in myeloid differentiation. In a recent study Kurotaki et al, 2022 determined the higher-order chromatin structure in DC progenitors, cDC1 and cDC2 on a genome-wide scale by Hi-C. In this study, reorganization of chromatin conformation at DC-specific gene loci was observed during cDC differentiation, and IRF8 was found to promote chromatin activation in DC progenitors leading to cDC lineage-specific gene expression.…”
Section: Introductionmentioning
confidence: 83%
“…During DC differentiation, the Irf8 gene locus shows high epigenetic dynamics, including histone modifications and TF binding identified by ChIP-seq ( Chauvistré and Seré, 2020 ; Durai et al, 2019 ; Grajales-Reyes et al, 2015 ; Lin et al, 2015 ), chromatin accessibility measured by ATAC-seq ( Kurotaki et al, 2019 ; Li et al, 2019 ), and three-dimensional chromatin structure remodeling determined by chromosome conformation capture (3 C) ( Kurotaki et al, 2022 ; Schönheit et al, 2013 ). All this emphasizes the impact of epigenetic regulators on Irf8 gene activity in DC differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Cell-type-specific variations in the genome architecture are reflected in the compartment structure [12,[71][72][73]. These observations posit a conundrum: do compartments drive gene expression or vice-versa?…”
Section: Discussionmentioning
confidence: 99%
“… 81 , 82 Furthermore, we observed that most changes in gene expression occur without compartment changes. Similarly, most changes in gene expression occur in stable compartments during differentiation of mouse dendritic cells 83 and during sex differentiation in the Barbados nut tree. 84 Thus, although compartments are globally associated with gene expression, compartment switch and gene expression changes are correlated only at a subset of loci.…”
Section: Discussionmentioning
confidence: 99%